2021
DOI: 10.3390/met11020204
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Damage and Life Prediction Models for High-Cycle Fatigue of Metals: A Review

Abstract: Fatigue design of engineering structures is typically based on lifetime calculation using a cumulative damage law. The linear damage rule by Miner is the universal standard for fatigue design even though numerous experimental studies have shown its deficiencies and possible non-conservative outcomes. In an effort to overcome these deficiencies, many nonlinear cumulative damage models and life prediction models have been developed since; however, none of them have found wide acceptance. This review article aims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(52 citation statements)
references
References 136 publications
0
39
0
Order By: Relevance
“…The equivalent stress amplitudes were calculated by Formula (7), with k = 0.68 for all determined components. The damage rate, D MDSM , was determined by the linear cumulative damage (Palmgren-Miner’s) rule [ 54 ]. It was observed that the highest impact on the damage rate was the primary cycle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The equivalent stress amplitudes were calculated by Formula (7), with k = 0.68 for all determined components. The damage rate, D MDSM , was determined by the linear cumulative damage (Palmgren-Miner’s) rule [ 54 ]. It was observed that the highest impact on the damage rate was the primary cycle.…”
Section: Resultsmentioning
confidence: 99%
“…the obtained data describing the identified stress cycles for a given waveform are the basis for further fatigue analysis, using the chosen stress cumulation hypothesis, i.e., Palmgreen-Miner’s [ 36 , 37 , 38 , 52 , 53 , 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…The proposed probability-based model was applied to predictions of damage degree in different conditions. Here, the model was established for 1.0570 steel and two alumin ium alloys, LY12-CZ and 2524-T3, according to Equation ( 3), the design s-n curves in Equation (10) and Table 1, and the parameter estimation results listed in Section 4.1, as well as Tables 2-5. The calculated values of damage degree were further compared to the values calculated according to Miner's rule.…”
Section: Resultsmentioning
confidence: 99%
“…As can be seen, Miner's rule is based on a linear model of damage accum Although Miner's rule is widely used in the case of metallic materials because it is implement and computationally inexpensive, an issue was raised concerning the of the critical damage degree [1]. Linear damage accumulation rules, under cert cumstances (e.g., sequential loading effects, notches, non-standard environmen produce significant and unusual scatter, corresponding to the scatter band equal t or even more [9,10]. Non-linear damage accumulation rules offer more accurate o conservative predictions than the linear rules [9,10].…”
Section: Relation Between Fatigue Damage Accumulation and Fatigue Lifementioning
confidence: 99%
See 1 more Smart Citation